IDENTIFICATION OF WORK ACCIDENT RISK OF TRAY CABLE INSTALLATION IN X APARTMENT PROJECT - Widodo, Eko Wahyu; Mandagi, Ayik Mirayanti (Majalah Kesehatan Masyarakat Aceh (MaKMA), 2020)
Work accidents that occured in Indonesia, 32% are accidents from the construction sector. The construction  sector is a sector with a work environment where there were so many hazard risks. Cable tray installation is one of the jobs in a construction project. The purpose of this research is to get an overview of the steps in the installation of cable tray and the its risk. The process of identifying work accident risk in this study uses Job Safety Analysis (JSA). Falling from height is one of the workplace accidents in the cable tray installation process. Risk control is needed to prevent work accidents that can occur due to cable tray installation.